Media Relations dan Kepuasan Wartawan Atas Layanan Kehumasan di Kabupaten Brebes - Isni, Lusiana Indira (Interaksi: Jurnal Ilmu Komunikasi, 2012)
AbstractMedia relations as a specific activity of the PR to communicate messages, or specific information about the activities that are institutional, corporate / institutional, product and other individual to activities that need to be published in cooperation with the press / media to create publicity and positive image. Therefore, a public relations practitioner must be able to establish good relations with the mass media for smooth performance. In dealing with a mass media public relations officer to work in a professional, credible, and ability to establish good relationships with journalists and the media. This study aims to determine the extent of the influence of public relations officers role in media relations activity that consists of variable credibility, professionalism and interpersonal relations between public relations officers and journalists - to the satisfaction of journalists upon public relations services This study uses explanatory research. The hypothesis of this study is that there is the influence of credibility, professionalism, and level of interpersonal relations betweenÂ  public relations officers and journalists to the satisfaction of journalists upon public relations services. The results showed the value of coefficient of determination (R2) which shows the magnitude of the effect the credibility of public relations officers, public relations officer professionalism, the level of interpersonal relationships between journalists and public relations officer to the journalists satisfaction upon public relations services is 81.1%. It can be concluded that journalists satisfaction is heavily influenced by the credibility of public relations officer, the professionalism of public relations officers, and the interpersonal relationship between public relations officers and journalists.Â Keywords: media relations, role of public relations officers, journalists satisfaction